Predicting the effectiveness of methotrexate therapy based on basal expression of the AMP-activated protein kinase gene in the blood of patients with rheumatoid arthritis - E. V. Chetina; N. V. Demidova; G. A. Markova; E. P. Salyanova (Современная ревматология)
Objective: to search for an association between basal expression of the AMP-activated protein kinase (adenosine monophosphate-activated protein kinase, AMPK) gene in the blood of patients with rheumatoid arthritis (RA) and disease activity, as well as joint destruction before and after 24 months of methotrexate (MT) therapy.Patients and methods. The study included 40 patients with RA who met the 1987 ACR classification criteria, with a disease duration of not more than 2 years, with a mean age of 47.5±15.5 years. All patients received 15 mg/week of MT. The number of swollen joints (SJC) out of 44, the number of tender joints (TSC) out of 53, the duration of morning stiffness (in minutes) and RA activity were assessed using the DAS28 index. The concentration of CRP and IgM rheumatoid factor (RF), antibodies to cyclic citrullinated peptide (ACCP) were assessed. To evaluate the radiological progression of RA, the Sharp method modified by van der Heijde was used. Gene expression in peripheral blood cells was determined by reverse transcriptase reaction and real-time polymerase chain reaction.Results and discussion. During MT therapy, there was a decrease in disease activity by DAS28 index, CRP level, duration of morning stiffness, SJC and TJC. After 2 years, there were no statistically significant changes in the number of erosions, while the number of joints with narrowing of the joint space increased by the end of the study (p=0.004). Treatment with MT resulted in a decrease in AMPK expression. At the same time, patients who achieved remission had the highest level of AMPK before therapy, as did seronegative patients compared to seropositive ones. Based on the ROC analysis, the threshold value of AMPK gene expression was determined, which makes it possible to predict a high probability of a positive effect of MT therapy.Conclusion. AMPK gene expression is associated with disease activity. Its high initial blood level in RA patients is associated with greater efficiency of MT and, possibly, plays a protective role. With an AMPK gene expression index greater than 3.83, the probability of a positive response to MT is high.